Revision of the Brazilian Northeastern Cleistepyris (Hymenoptera: Bethylidae), with description of six new species - Jr., Wilson J. Marques; Azevedo, Celso O.; Colombo, Wesley D. (Zootaxa, 2025)
The recently revalidated genus Cleistepyris Kieffer is revised based on specimens collected in the Brazilian Savannah (Cerrado), Caatinga and Atlantic Rainforest deposited in the Coleção Zoológica do Maranhão (CZMA). A total of 16 species are recognized, ten of which correspond to previously described species: C. clypeatus (Leal & Azevedo), C. inca (Evans), C. megaventris (Azevedo & Batista), C. neotropicus (Evans), C. ocullatus (Azevedo & Batista), C. paraensis (Kieffer), C. quadratus (Evans), C. quelatus (Ramos, Araújo & Azevedo), C. spinipes (Evans), and C. santacatarinae (Evans). In addition, six new species are described and illustrated: C. awaguaja Marques, Azevedo & Colombo, sp. nov., C. guajajara Marques, Azevedo & Colombo, sp. nov., C. kanela Marques, Azevedo & Colombo, sp. nov., C. piripiri Marques, Azevedo & Colombo, sp. nov., C. tenetehara Marques, Azevedo & Colombo, sp. nov., and C. tremembe Marques, Azevedo & Colombo, sp. nov. A taxonomic key is provided for all species included in this study. The morphology of the genus is discussed, emphasizing species diagnostic characters, particularly those of the male genitalia, based on aedeagus, dorsal margin of cuspis and harpe. Distributional data are also presented, contributing to a better understanding of the biogeography of Cleistepyris in the Neotropical region and Brazilian ecosystems. The results reveal significant morphological variation, mostly in the male genitalia suggesting the potential for future taxonomic refinement with a narrow focus the group, including the possible recognition of new genera.